LOKASI SENAM LANSIA BERPERAN PENTING TERHADAP PARTISIPASI LANSIA DALAM MENGIKUTI KEGIATAN SENAM - Dwi Agustina (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Background: The increasing number of elderly people needs special attention particularly to improve the quality of their lives. Elderly gymnastic at Posyandu is one of the government's efforts to achieve a healthy old age. Elderly gymnastics affect the increase in musculoskeletal fitness, associated with increased general health status, reducing the risk of chronic disease and disability. Objective: To identify the influencing factors of elderly gymnastics participation at Posyandu. Methodology: Descriptive analytical observational with cross sectional approach. Research conducted at the Elderly Posyandu in Puskesmas Jatiwarna Bekasi working area on August - November 2015. Data analysis included univariate, bivariate with Chi Square, multivariate with binary logistic regression enter method. Results: Most elderly (59%) participated elderly gymnastics regularly. Variable Posyandu distance <0.5-1 km was the most dominant variables contributed to the OR at 11 times greater than those who lived within < 0,5km from posyandu. Conclusion: To attract elderly participate gymnastics elderly regularly, the elderly gymnastic activities should be carried out as close as possible to the residence of the elderly